The needs of children : Multiperspective study - Yanti Kusuma; Naimah Naimah (Journal of Early Childhood Care and Education (JECCE), 2021)
Every human being has various needs in his life, as well as in children. Essential basic needs in children must be met so that children grow and develop optimally, but the discussion of various perspectives on children's basic needs still needs to be reviewed. Therefore, this article aims to analyze the theories of needs, the concept of basic human needs, and the needs of early childhood from scientific and Islamic studies. Literature study was used in this study. The research results obtained by students have the same needs as humans in general. Children will be happy when they are cared for, cared for, considered to exist, not discriminated against, rewarded for achievements that have been achieved, can increase self-confidence, and foster a sense of caring among others, as well as have broad insight and train children to be able to increase courage.